2021
DOI: 10.3389/fpsyg.2021.605059
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interested Framed and Prosocially Framed Messaging Can Equally Promote COVID-19 Prevention Intention: A Replication and Extension of Jordan et al.’s Study (2020) in the Japanese Context

Abstract: How can we effectively promote the public’s prevention of coronavirus disease 2019 (COVID-19) infection? Jordan et al. (2020) found with United States samples that emphasizing either self-interest or collective-interest of prevention behaviors could promote the public’s prevention intention. Moreover, prosocially framed messaging was more effective in motivating prevention intention than self-interested messaging. A dual consideration of both cultural psychology and the literature on personalized matching sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…Finally, while our interventions were grounded in theory on moral foundations and wise interventions, it is possible that there are other interventions that would have been more effective. There is some evidence, for example, that using messages that focus on the community-wide benefits of face coverings ( Capraro & Barcelo, 2020 ), promote reasoning over emotional responses ( Capraro & Barcelo, 2021 ), discuss COVID-19 as a public (vs. personal) threat ( Jordan et al, 2020 ; c.f., Miyajima & Murakami, 2021 ), evoke empathy through storytelling about how the virus affected the elderly ( Pfattheicher, Nockur, Böhm, Sassenrath, & Petersen, 2020 ), or use written reflection exercises ( Hume, John, Sanders, & Stockdale, 2020 ) show some efficacy in promoting COVID-19 health behaviors. Future research using meta-analysis will be useful in discerning which interventions had the most powerful impact during COVID-19 and whether they were effective for both Republicans and Democrats.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while our interventions were grounded in theory on moral foundations and wise interventions, it is possible that there are other interventions that would have been more effective. There is some evidence, for example, that using messages that focus on the community-wide benefits of face coverings ( Capraro & Barcelo, 2020 ), promote reasoning over emotional responses ( Capraro & Barcelo, 2021 ), discuss COVID-19 as a public (vs. personal) threat ( Jordan et al, 2020 ; c.f., Miyajima & Murakami, 2021 ), evoke empathy through storytelling about how the virus affected the elderly ( Pfattheicher, Nockur, Böhm, Sassenrath, & Petersen, 2020 ), or use written reflection exercises ( Hume, John, Sanders, & Stockdale, 2020 ) show some efficacy in promoting COVID-19 health behaviors. Future research using meta-analysis will be useful in discerning which interventions had the most powerful impact during COVID-19 and whether they were effective for both Republicans and Democrats.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, not all studies looking at the relationship between prevention behavior and collectivism lend support to the narrative outlined above. Several studies have found that individualism also contributes to the uptake of COVID-19 prevention behaviors (Galang, Johnson, & Obhi, 2021 ; Miyajima & Murakami, 2021 ; Mo & Park, 2021 ; Shekriladze, Javakhishvili, & Chkhaidze, 2021 ; Xiao, 2021 ) – after all falling ill to COVID-19 is not usually in one’s self-interest. This raises questions about the role that culture plays in influencing individual behavioral responses to COVID-19.…”
Section: The Role Of Personality In the Covid-19 Pandemicmentioning
confidence: 99%
“…The channels through which this can occur are diverse; culture influences our decisions by altering not only the consequences of our choices, but the very way in which those choices are framed and conceptualized. For instance, Miyajima and Murakami (2021) show how culture influences the efficacy of self-interested versus pro-social public health messaging in the Japanese context.…”
Section: Hypothesis Developmentmentioning
confidence: 99%